Lnc-TALC promotes O6-methylguanine-DNA methyltransferase expression via regulating the c-Met pathway by competitively binding with miR-20b-3p - Pengfei Wu (Nature Portfolio, 2019)
Temozolomide resistance in glioblastoma is associated with MGMT overexpression. Here, the authors identify a lncRNA that is a competitive endogenous RNA for miR-20b-3p, which causes c-Met activation to modulate acetylation of histone H3 on MGMT promoter through Stat3/p300 complex to increase MGMT expression and temozolomide resistance.